k-10=-53/5

Simple and best practice solution for k-10=-53/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k-10=-53/5 equation:


k in (-oo:+oo)

k-10 = -53/5 // + -53/5

k-(-53/5)-10 = 0

k+53/5-10 = 0

k+3/5 = 0 // - 3/5

k = -3/5

k = -3/5

See similar equations:

| w+5=62/11 | | d+5/8=-1/24 | | b+1/9=-23/36 | | t/4=-2/3 | | -2/7w=-2/63 | | -7/24=a-2/3 | | a-3/8=-59/8 | | -1/3m=-1/10 | | t-2/7=40/7 | | m-5=-15 | | w+1=11 | | n+1/5=13/15 | | 2/3t=-6 | | -7+k=-8 | | 2/7x=-12/7 | | -5/8+w=27/8 | | b-1/6=-3/4 | | -8+m=-15/2 | | 1/2n=-6 | | t+2/5=-3/5 | | 2/5x=-18/5 | | a/-2=-4 | | -1+d=-2 | | 5m=25/11 | | -1+a=-1 | | t+1/2=21/22 | | 4x/2=6 | | 7*x^2+4x=0 | | -3/5m=21/50 | | x+2/5=-53/5 | | 5/4=t+2 | | w/4=-5 |

Equations solver categories